Motivations for prescription drug misuse among young adults: Considering social and developmental contexts. (June 2015) - LeClair, Amy; Kelly, Brian C.; Pawson, Mark; Wells, Brooke E.; Parsons, Jeffrey T.
Abstract Aims: This study aimed to explore motivations for prescription drug (i.e. prescription pain killers, stimulants and sedatives) misuse among young adults active in urban nightlife scenes in New York City. Prior research has established "recreation" and "self-medication" as the primary motivations among this age group, but, as prescription drug misuse continues to be a major public health concern in the US and rates of misuse are highest among young adults, a more nuanced analysis is necessary for developing meaningful interventions. As part of a larger study on prescription drug misuse among young adults active in urban nightlife scenes, we examined participants' motivations for misuse. Prescription painkillers, stimulants and sedatives were the primary substances of interest. Methods: Participants were recruited from nightlife venues in New York using time-space sampling. Subjects completed a mixed-methods assessment at project research offices. The data presented here are from a subsample of 70 qualitative interviews conducted during the baseline assessment. Findings: We identified experimentation and a "work hard, play hard" ethos as key motivations for misusing prescription drugs and argue that these motivations are specific, though not necessarily unique, to the participants' social location as young adults. These findings highlight the role of life stage and social context in the misuse of prescription drugs. Conclusion: Future studies of prescription drug misuse should pay attention to the larger social contexts in which users are embedded and, therefore, make decisions about how and why to misuse. Moving beyond the very broad concepts of "recreation" and "self-medication" presently established in the research, policies targeting young adults should include educational components focused on denormalising prescription drugs, and interventions should be tailored to transitional contexts and the associated motivations those contexts foster.